Modulation of intracellular expression of IFNγ and IL-2 in culture of splenic T lymphocytes by some flavonoid glycosides of Alchornea floribunda. (1st September 2016) - Okoye, Festus B. C.; Odimegwu, Damian Chukwu; Nworu, Chukwuemeka Sylvester; Agbo, Matthias Onyebuchi; Esimone, Charles Okechukwu; Osadebe, Patience Ogoamaka; Proksch, Peter
Abstract: Context Alchornea floribunda Müll. Arg. (Euphorbiaceae) leaves are widely used in ethnomedicine for the management of rheumatism, arthritis and toothache. Objective In this study, flavonoid glycosides isolated from Alchornea floribunda were screened for their effect on the intracellular expression of interferon-gamma (IFNγ) and interleukin-2 (IL-2) type-1 cytokines. Materials and methods Chromatographic purification of the ethyl acetate fraction of the methanol leaf extract led to the isolation of seven flavonoid glycosides (1 –7 ). Their structures were elucidated by 1D and 2D nuclear magnetic resonance and mass spectrometry. Splenocytes were treated with graded concentrations of the compounds (6.25–25 μg/mL) and incubated for 24 h. Thereafter, their effect on the expression of IFNγ and IL-2 by CD4 +  and CD8 +  T-lymphocytes was evaluated using intracellular cytokine staining and FACS analysis. Results Compounds1 –7 (6.25–25 μg/mL) caused the up-regulation of activated CD8 +  (57.85–72.45% versus 57.85% for untreated control) and, to a lesser extent, activated CD4 +  (3.21–7.21% versus 2.75% for the untreated control) T-lymphocytes that were both largely interferon-gamma-releasing in treated mouse T lymphocytes relative to untreated control. FACS data analysis showed that stimulation with all the compounds increased the proportion of CD8 + /IFNγ +  and CD4 + /IFNγ +  T lymphocytes up to two-fold when compared with the cells in untreated control wells. Intracellular IL-2 secretion by treated T cells was not detected. Conclusion This recorded T-lymphocyte-specific immune-modulatory property may contribute to explain in part the dynamics associated with the ethnomedicine of Alchornea floribunda, and may find relevance as a necessary cellular immune response precursor to infection-associated disease management.